Representasi Gender Pada Karakter Hero dalam Game League of Legends - Zahwa Afifah (Jurnal Ilmu Komunikasi, 2022)
Often, video game characters are designed to fit their gender expectations, this correlation between character design and gender has not been fully explored. This research investigates the representation of characters from various perspectives, exploring elements of character design specifically in MOBA video games League of Legends due to their popularity and gameplay similarities. This study uses a qualitative research method with Charles Sanders Pierce's semiotic analysis. Data analysis was categorized into three parts, namely character ability mechanics, character lore, and visual representation of character avatars in MOBA League of Legends video games. This research is presented in three core studies, the first investigates the mechanics of character abilities in the form of gameplay abilities. Research has found that male characters are more likely to have abilities that allow them to be independent, whereas female characters have more abilities that assist their allies in play, inherently placing them in submissive roles. The second part of the research explores the relationship between gender and character narratives. This study evaluates the character's lore and identifies the themes used in the character's storyline. The results find that female characters are represented as someone who is vulnerable. However, as their story progresses there are character developments where they are often praised for being stubborn, independent, and strong. Male characters are depicted as strong figures, namely typical masculinity such as not being allowed to cry, not being weak, and must lead. The third and final section examines the visual appearance of the characters. This study identified a correlation between the number of gender characters with skins displayed and players' perceptions of the sexiness and attractiveness of the characters. The findings from the third part of the research indicate areas where gender influences the design of the existing characters. This research could have a real-world impact on future character creations.